HYBRID REVASCULIZATION AS METHOD OF SURGICAL TREATMENT OF ISCHEMIC CORONARY DISEASE IN NUMEROUS LESIONS OF CORONARY BED - K. L. Koslov; A. N. Shishkevich; V. N. Kravchuk; S. S. Mikhailov; E. A. Knyazev; I. B. Oleksyuk (Вестник хирургии имени И.И. Грекова)
Hybrid revasculization of myocardium combined the advantages of mammary-coronary bypass surgery and coronary arteries stenting. It presented itself as a perspective direction in treatment of ischemic coronary disease. The article provides the results of comparison of usage of hybrid revasculization of myocardium and aortocoronary bypass in 71 patients with multivessel coronary artery disease. The data obtained indicated, that hybrid approach allowed complete revasculization of the myocardium (as in case of aortocoronary bypass), fast recovery of the patient, shortening a hospital stay due to decrease of intra- and postoperative complications.